Introduction to modeling in physiology and medicine - Cobelli, Claudio (Academic Press series in biomedical engineering., 2008)
This unified modeling textbook for students of biomedical engineering provides a complete course text on the foundations, theory and practice of modeling and simulation in physiology and medicine. It is dedicated to the needs of biomedical engineering and clinical students, supported by applied BME applications and examples. Developed for biomedical engineering and related courses, with an interdisciplinary clinical/engineering approach, quantitative basis, and many applied examples to enhance learning Delivers a quantitative approach to modeling and also covers simulation Case studies and engineering applications from BME, plus end of chapter exercises and Instructors manual.